Peran Keadilan Organisasi dalam Membangun Komitmen Organisasi untuk Meningkatkan Kinerja Karyawan - Ela Dina; Helmi Buyung Aulia Safrizal (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
This study discusses the commitment and performance of skiving employees at PT Karyamitra Budisentosa in the midst of organizational justice problems. This study is used to examine more deeply about the role of organizational justice in building organizational commitment to improve employee performance. This study uses qualitative research method to dig up information on the problems experienced by subjects of the study, namely organizational justice, organizational commitment, and employee performance. The writer uses 7 people as informants for different positions. Technique of collecting data uses the method of observation, method of interview, and method of documentation. The data validity test uses a credibility test using several techniques, namely persistence of observation, triangulation, reference materials, and member check. Technique of analyzing data consists of several processes, starting from data collection, data reduction, data presentation, to verification or drawing conclusions. The results of the study show that the role of organizational justice in building organizational commitment is through perception and trust in PT Karyamitra Budisentosa. When organizational commitment has been built on employees, then in the process of improving performance, this commitment plays a role in creating a sense of responsibility. Based on the results of the study, the writer provides suggestions for PT Karyamitra Budisentosa to take quick and appropriate action in creating organizational justice, because of the important role of organizational justice in the company.